O ensino de inglês por meio da poesia - Pinheiro, Ana Gabriele Borques (2024)
The teaching of an additional language (AL) should go beyond the mere mastery of grammar structures and vocabulary. Teaching supported by a variety of approaches and resources can broaden learning possibilities, addressing the diverse learning styles of students. In this context, this study explores the potential of English poetry in AL teaching, considering its relevance to the integral development of learners. The primary aim of this work is to discuss how poetry can contribute to the development of linguistic, socio-emotional, critical thinking, and creative competencies. This research, of bibliographic and exploratory nature, is based on references from applied linguistics, literature, and education, as well as the Brazilian National Common Curricular Base (BNCC). The study is structured into three main sections: a discussion of theoretical conceptions and official documents, Poetry, literary literacy, and English teaching, and a practical proposal for a pedagogical plan for reading poetry in English. The results indicate that poetry transcends its literary genre, emerging as a transformative textual genre. Its possibilities include connecting learners to the language in meaningful ways, stimulating critical and creative skills, and fostering a more collaborative and inclusive educational environment focused on student protagonism.